Detailed Pharmacognostical and Phytochemical Investigation on Soymida febrifuga Roxb ROOT BARK - Ananta Krushna Palei, Dr (International Journal of Pharmaceutical & Biological Archive, 2012)
Detailed Pharmacognostical and Phytochemical Investigation on Soymida febrifuga Roxb ROOT BARK